Translation and psychometric evaluation of a scale to measure the fear of activity in Chinese patients with coronary artery disease - Jiehong Chen; Wei Guo; Hongmei Liu; Wenhui Liu; Junjie Chen; Chunhua Ma (Nursing Open, 2023)
Abstract Aim To translate and test the psychometric properties of a Chinese version scale to measure the Fear of Activity in patients with Coronary Artery Disease. Design A cross‐sectional design. Methods The translation of the scale to measure Fear of Activity in Patients with Coronary Artery Disease included three steps, forward‐back translation, expert discussion and pilot survey. The internal consistency and test–retest reliability were used to assess the reliability of the Chinese version scale of the Fear of Activity. Content, construct, criterion, and known‐group validity of the scale were also evaluated. Data Sources A total of 275 patients with Coronary Artery Disease were recruited from a university‐affiliated hospital in Guangzhou, southern China. Results The overall content validity index of the Chinese version scale of the Fear of Activity in Patients with Coronary Artery Disease was 0.90. Principal component analyses extracted four factors with a cumulative variance contribution of 57.5%. There is a strong correlation (r = 0.83) between this scale and Tampa Scale for Kinesiophobia Heart. The total scores of the Chinese version scale of the Fear of Activity in female patients were higher than those in male patients with Coronary Artery Disease, indicating that the scale was able to distinguish the differences between low and high score groups. The Internal consistency and test–retest reliability coefficients of the scale were 0.74 and 0.82, respectively. Conclusion The Chinese version scale of the Fear of Activity in Patients with Coronary Artery Disease, which consists of 21 items with four dimensions, is a reliable and valid instrument to evaluate the fear of activity in patients with Coronary Artery Disease. Implications for the Profession and/or Patient Care The Chinese version scale of the Fear of Activity in Patients with Coronary Artery Disease can be used to assess the levels of fear of activity in patients with Coronary Artery Disease and explores the factors that influence fear of activity in the population. Impact This study translates and confirms the psychometric properties of the Chinese version scale of the Fear of Activity in Patients with Coronary Artery Disease in China. It is useful in both research and clinical fields to explore the fear of activity and its associated factors in patients with Coronary Artery Disease. Reporting Method The study design followed the guideline of Strengthening the Reporting of Observational Studies in Epidemiology statement. Patient or Public Contribution Patients in a university‐affiliated hospital participated in this study and contributed to data collection.